The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12013-014-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dexmedetomidine Post-treatment on the Inflammatory Response of Astrocyte Induced by Lipopolysaccharide

Abstract: To explore the effect of dexmedetomidine (DEX) post-treatment on the inflammatory response of astrocyte induced by lipopolysaccharide (LPS). The astrocytes of neonatal mice were primarily cultured in vitro. After purification and identification, the cells were divided into five groups: group C: control group; group L: astrocytes were treated with 1 μg/ml LPS for 24 h; group D1, D2, and D3: astrocytes were pretreated with 1 μg/ml for 24 h LPS, and then cultured with low (0.1 μM), medium (1 μM), high (10 μM) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In sepsis rats, Taniguchi et al [102] found that the medium dose (5 μg/kg/h) and high dose (10 μg/k/h) of DEX reduce plasma levels of TNF-α and IL-6, while the low-dose group (2.5 μg/kg/h) showed no decreasing effect. Similar experimental phenomena were observed in vitro [43,103]. Lai et al [104] believed that the anti-inflammatory effect of DEX had a parabolic relationship with its concentration.…”
Section: Correlation Of Anti-inflammatory Effects With Timing and Dosesupporting
confidence: 65%
“…In sepsis rats, Taniguchi et al [102] found that the medium dose (5 μg/kg/h) and high dose (10 μg/k/h) of DEX reduce plasma levels of TNF-α and IL-6, while the low-dose group (2.5 μg/kg/h) showed no decreasing effect. Similar experimental phenomena were observed in vitro [43,103]. Lai et al [104] believed that the anti-inflammatory effect of DEX had a parabolic relationship with its concentration.…”
Section: Correlation Of Anti-inflammatory Effects With Timing and Dosesupporting
confidence: 65%
“…In our previous study, dexmedetomidine reduced mechanical allodynia and hyperalgesia in a chronic constriction injury model of neuropathic pain [Farghaly et al, 2014]. Another study revealed that dexmedetomidine reduced hippocampal levels of cytokines in various pain conditions [Tanabe et al, 2014;Xie et al, 2015;Farghaly et al, 2016;Zhu et al, 2016]. They suggested that stimulation of α 2 -receptors during stress causes modulation of cytokine production by monocytes and macrophages, independently of adenylyl cyclase cAMP.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to its sedative and analgesic effects, many studies proved its anti-inflammatory effect. It attenuates lipopolysaccharide-induced cytokine expression in astrocytes [Xie et al, 2015]. Through α 2A -adrenergic receptors, it suppresses mRNA of MCP-1, a proinflammatory cytokine [Liu et al, 2017].…”
Section: Abbreviations Used In This Papermentioning
confidence: 99%
“…The effects of dexmedetomidine on inflammation have been demonstrated in some clinical settings and studies. Medium and high concentrations of dexmedetomidine inhibited the expression and release of inflammatory factors in mice 11 . Adult patients receiving a 1.0 μg/kg loading dose of dexmedetomidine followed by infusion at 0.5 μg/kg/h for laparoscopic cholecystectomy showed a decreased inflammatory response 12 .…”
Section: Introductionmentioning
confidence: 99%